How I approach new onset thrombocytopenia. (2nd April 2020) - Swain, Fiona; Bird, Robert
Abstract: Thrombocytopenia is a common reason for referral to hematologists in community and hospital practice. A broad differential diagnosis, combined with the potentially life-threatening nature of some presentations necessitates a rapid evaluation of the situation and potential need for emergency intervention; followed by further comprehensive investigation to confirm the diagnosis and institution of longer term management. This review offers an approach to the initial assessment, diagnosis, and referral. We then highlight aspects of the clinical history, examination and laboratory investigations which may provide critical insights into the most likely diagnosis. ITP is the commonest cause of severe isolated thrombocytopenia in the general community and is the most common cause of thrombocytopenia in patients referred to our hematology service. It remains a diagnosis of exclusion and a high degree of vigilance for alternative diagnoses should be maintained, particularly if presentations are atypical or expected response to treatment is not seen. Adult presentation of hereditary thrombocytopenia syndromes can mimic new onset thrombocytopenia, however, improving access to genetic testing will facilitate accurate diagnosis and avoid unnecessary treatment.